2010
DOI: 10.1109/tbme.2010.2053929
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Detrended Moving-Average Method for Monitoring the Depth of Anesthesia

Abstract: The detrended moving-average (DMA) method is a new approach to quantify correlation properties in nonstationary signals with underlying trends. This paper monitored the depth of anesthesia (DoA) using modified DMA (MDMA) method. MDMA provides a power-law relation between the fluctuation function F(MDMA)(s) and the scale s: F(MDMA)(s)αs(α), where α is the slope of F(MDMA)(s) in the logarithm scale. We applied the MDMA to monitor the DoA by computing the scaling exponent F(α) and F(min) values. To validate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Kantelhardt et al, proposed the MDFA method to describe the non-stationary time series, which is based on a generalization DFA method (Kantelhardt et al, 2002 ). Nguyen-Ky et al, used the moving-average DFA method to monitoring the DoA and the results showed that DFA could accurately estimate a patient's hypnotic state (Nguyen-Ky et al, 2010a ).…”
Section: Materials and Statistical Methodsmentioning
confidence: 99%
“…Kantelhardt et al, proposed the MDFA method to describe the non-stationary time series, which is based on a generalization DFA method (Kantelhardt et al, 2002 ). Nguyen-Ky et al, used the moving-average DFA method to monitoring the DoA and the results showed that DFA could accurately estimate a patient's hypnotic state (Nguyen-Ky et al, 2010a ).…”
Section: Materials and Statistical Methodsmentioning
confidence: 99%
“…For an accurate and reliable depth of anesthesia assessment, intensive research has been conducted, and various algorithms were developed. The latest methods includes Entropy [7], Detrended moving-average (DMA) [8], Isomap-based estimation [9], Empirical-mode decomposition (EMD) [3], and Bayesian [10]. Nguyen-Ky developed a new technique to rectify the problems of BIS by developing a wavelet-based depth of anesthesia (WDoA) with a help of discrete wavelet transform(DWT) and power spectral density function (PSD) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [8] and Ferenets et al [9] adopted nonlinear methods to quantify EEG variations during anaesthesia. To overcome the difficulties of DFA in discriminating between wakefulness and deep anaesthesia, Nguyen-Ky et al [10] developed an improved detrended moving-average method, while Palendeng et al [11] used the phase and amplitude of EEG signals as measures of DoA.…”
Section: Introductionmentioning
confidence: 99%